Persepsi dan Partisipasi Masyarakat terhadap Ekosistem Mangrove di Distrik Sorong Timur, Kota Sorong Provinsi Papua Barat - Handayani Handayani; Mustasim Mustasim; Amir M Suruwaky (Jurnal Airaha, 2020)
This research is a study of people's perceptions and participation of mangrove ecosystems in East Sorong District, Sorong City. The study uses descriptive methods with questionnaire and observation data collection techniques. Data processing is done by tabulation and expressed in the form of graphs and diagrams. The results showed 63% of respondents stated that the mangrove ecosystem in their area had diminished. Respondents' perception of mangrove harvesting for firewood needs stated 44% agreed and disagreed 48%, while community perceptions about mangrove cutting for building materials 53% disagreed and 40% agreed. In relation to the conversion of ecosystem functions into ponds / settlements, 65% of respondents disagree. Community participation in the preservation of mangrove ecosystems is very low at 83%. The community hopes for the socialization of the Sorong City Government or observers of the environment in the conservation of mangrove ecosystems.